2019
DOI: 10.1111/jcpp.13009
|View full text |Cite
|
Sign up to set email alerts
|

The importance of theDSM‐5posttraumatic stress disorder symptoms of cognitions and mood in traumatized children and adolescents: two network approaches

Abstract: Background The aim of this study is to provide a better understanding of the central symptoms of DSM‐5 posttraumatic stress disorder (PTSD) in children and adolescents from the perspective of the child and its caregiver. Identifying core symptoms of PTSD can help clinicians to understand what may be relevant targets for treatment. PTSD may present itself differently in children and adolescents compared to adults, and no study so far has investigated the DSM‐5 PTSD conceptualization using network analysis. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 34 publications
9
44
1
1
Order By: Relevance
“…Most of the participants in Bartels et al. 's study () reported interpersonal trauma (55.5%) compared with 18.9% in our sample. Furthermore, in line with our findings, strong physical sensations had previously emerged as a central symptom in another network analysis of PTSD symptoms in children and adolescents exposed to disasters (Russell, Neill, Carrion, & Weems, ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Most of the participants in Bartels et al. 's study () reported interpersonal trauma (55.5%) compared with 18.9% in our sample. Furthermore, in line with our findings, strong physical sensations had previously emerged as a central symptom in another network analysis of PTSD symptoms in children and adolescents exposed to disasters (Russell, Neill, Carrion, & Weems, ).…”
Section: Discussioncontrasting
confidence: 56%
“…Using DSM‐5 PTSD symptoms, Bartels et al. () found that symptoms of the negative alterations in cognitions and mood cluster emerged as central in their network. However, also psychological distress (B4, DSM‐5) and avoidance of thoughts or memories (C1, DSM‐5) emerged as central.…”
Section: Discussionmentioning
confidence: 99%
“…Bartels et al. employ, amongst other things, a Bayesian approach to model directed acyclic graphs of post‐traumatic stress disorder (PTSD) symptoms in children and adolescents (Bartels et al., ). They demonstrate which symptoms of PTSD are the key drivers of other symptoms within PTSD and thus are able to advise, based on their data, which symptoms would be the optimal targets for treatment.…”
Section: It Is Full Steam Ahead For Genetic Research On the P Factormentioning
confidence: 99%
“…No exclusion criteria have been de ned for participants in the RCT. 4. To assess the costs of care for UYRs and the cost utility of the BETTER CARE model in comparison to usual care+.…”
Section: Participants and Eligibility Criteriamentioning
confidence: 99%